The Effects of the Internet and Mobile Services on Urban Household Expenditures - Aihua Zhang; Jia Lv; Ying Kong (International Telecommunications Society (ITS), 2017)
In recent years, the economy of China has entered a new normal state and the economic growth rate has decelerated. The telecommunications industry as a national strategic and basic industry, is also facing up with some dilemma. Information consumption is a comprehensive concept including e-commerce, communications, broadband services, online games and so on. On this basis, this paper employs the almost ideal demand system(AIDS) to explore the impact that information consumption has made to residential consumption expenditure and the change of the consumption structure. Ac-cording to empirical analysis, finally we can draw the following conclusions: The income elasticity of information consumption is greater than 1, which means the income demand is flexible. And the self-price elasticity of information consumption is negative and the absolute value is between 0 and 1. It means that the price of information consumption is not flexible.
Keywords: 330; Information consumption; Household consumption expenditure; The almost ideal demand system(AIDS); Demand elasticity Information consumption